Ferromagnetism induced by vacancies in (N, Al)-codoped 6H-SiC. (February 2019) - Lin, Long; Zhu, Linghao; Zhao, Ruiqi; Tao, Hualong; Huang, Jingtao; Zhang, Zhanying
Abstract: The electronic structures and magnetic properties of 6H-SiC doped with N, C vacancies ( V C ), Si vacancies ( V Si ) and Al are studied by first principles calculations. The results indicate that the N substituting C in 6H-SiC cannot order magnetism but V Si can introduce magnetic moments effectively. Ferromagnetism coupling is obtained in (N, 2 V Si )-codoped 6H-SiC. The ferromagnetism can be mainly attributed to the interactions between the 2 p orbitals of C atoms around Si vacancies. More interestingly, substituting Si with Al can enhance the ferromagnetic states in 6H-SiC in neutral states. We also studied the effect of charge on magnetic properties and provide an effective method of tuning magnetism in 6H-SiC. Highlights: The doping with NSi, VSi and (NC, VSi ) can induce ferromagnetism in 6H-SiC crystal. Ferromagnetism can be enhanced by Al substituting and charge. The spin polarization is proposed as the origin of ferromagnetism.